2011
DOI: 10.1016/j.breast.2010.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Discordance in early breast cancer for tumour grade, Estrogen Receptor, Progesteron Receptors and Human Epidermal Receptor-2 status between core needle biopsy and surgical excisional primary tumour

Abstract: The aim of the present study was to compare the tumour grade, Estrogen Receptor (ER), Progesteron Receptor (PgR) and Human Epidermal Receptor-2 (HER-2) status in the core needle biopsy (CNB) with those observed in the subsequent excisional primary tumour (EPT). All patients diagnosed with an early breast cancer in our University Hospital Center between January 1, 2005 and December 31, 2006 were included but exclusion criteria of patients with large tumour requiring neoadjuvant chemotherapy and cases with more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
57
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(69 citation statements)
references
References 15 publications
9
57
3
Order By: Relevance
“…It is suggested that upscoring may occur in CNB compared with excisional biopsy, probably due to better fixation in CNB than in surgical specimens [8], which was not confirmed in this study. Based on very good correlation (96.7%), sensitivity (100%), and specificity (91.66%), ER can be accurately assessed in CNB, which is in agreement with previous studies [9,16].…”
Section: Resultssupporting
confidence: 77%
“…It is suggested that upscoring may occur in CNB compared with excisional biopsy, probably due to better fixation in CNB than in surgical specimens [8], which was not confirmed in this study. Based on very good correlation (96.7%), sensitivity (100%), and specificity (91.66%), ER can be accurately assessed in CNB, which is in agreement with previous studies [9,16].…”
Section: Resultssupporting
confidence: 77%
“…The overall concordance between ER, PR, and HER2 by Oncotype DX (RT-PCR) and IHC/FISH has previously been shown to be high in prospectively designed large studies [23][24][25] using ASCO/CAP guidelines, although those concordance studies were performed using surgical specimens and not core biopsies. Importantly, discordant results with regard to ER and HER2 assessment by IHC in different laboratories are reported in the same range, and differences between core and surgical specimens are also commonly described [26]. These findings reinforce the need for quality control for pathological assessment and liberal repeated testing in discordant cases.…”
Section: Discussionmentioning
confidence: 58%
“…In cases achieving a pathological complete response with treatment, the prognostic and predictive molecular markers should be evaluated using core biopsy specimens [28]. However, it may be a concern if assessment in core needle biopsy is less reliable than in excisional biopsy owing to smaller sample size or heterogeneous tumour status [28][29][30]. If it is possible to predict triple-negative breast cancer on the basis of imaging features, this additional information could assist in both pretreatment planning and prognosis [17].…”
Section: Discussionmentioning
confidence: 99%